DOCK5 regulates energy balance and hepatic insulin sensitivity by targeting mTORC1 signaling. (29th December 2019) - Lai, Yerui; Zhao, Anjiang; Tan, Minghong; Yang, Mengliu; Lin, Yao; Li, Shengbing; Song, Jinlin; Zheng, Hongting; Zhu, Zhiming; Liu, Dongfang; Liu, Chaohong; Li, Ling; et al.
Abstract: The dedicator of cytokinesis 5 (DOCK5) is associated with obesity. However, the mechanism by which DOCK5 contributes to obesity remains completely unknown. Here, we show that hepatic DOCK5 expression significantly decreases at a state of insulin resistance (IR). Deletion of DOCK5 in mice reduces energy expenditure, promotes obesity, augments IR, dysregulates glucose metabolism, and activates the mTOR (Raptor)/S6K1 pathway under a high‐fat diet (HFD). The overexpression of DOCK5 in hepatocytes inhibits gluconeogenic gene expression and increases the level of insulin receptor (InsR) and Akt phosphorylation. DOCK5 overexpression also inhibits mTOR/S6K1 phosphorylation and decreases the level of raptor protein expression. The opposite effects were observed in DOCK5‐deficient hepatocytes. Importantly, in liver‐specific Raptor knockout mice and associated hepatocytes, the effects of an adeno‐associated virus (AAV8)‐ or adenovirus‐mediated DOCK5 knockdown on glucose metabolism and insulin signaling are largely eliminated. Additionally, DOCK5–Raptor interaction is indispensable for the DOCK5‐mediated regulation of hepatic glucose production (HGP). Therefore, DOCK5 acts as a regulator of Raptor to control hepatic insulin activity and glucose homeostasis. Synopsis: DOCK5 has been associated with obesity, however, the mechanism was not understood. This study reveals that DOCK5 reduces Raptor stability and mTORC1 activity in hepatocytes, thereby modulating hepatic insulin activity and glucose homeostasis. Hepatic DOCK5 expression is reduced in a model of HFD induced insulin resistance. DOCK5 deficient mice exhibit obesity, insulin resistance, reduced energy expenditure and hyperactive mTORC1 signaling on HFD. DOCK5 overexpression results in Raptor degradation and reduced mTORC1 signaling. Liver specific Raptor depletion reverses the effects of DOCK5 depletion. Abstract : DOCK5 has been associated with obesity, however, the mechanism was not understood. This study reveals that DOCK5 reduces Raptor stability and mTORC1 activity in hepatocytes, thereby modulating hepatic insulin activity and glucose homeostasis.